A growing impact of new parties: Myth or reality? Party system innovation in Western Europe after 1945. (September 2018) - Emanuele, Vincenzo; Chiaramonte, Alessandro
Despite the large body of literature on the emergence and success of new political parties in Western Europe, few, if any, attention has been paid to investigate new parties from a systemic perspective, therefore exploring their potential effects on party systems. This article focuses on party system innovation (PSInn), defined as the aggregate level of 'newness' recorded in a party system at a given election. After having reviewed the extant literature on the topic, the article discusses what a new party is and provides a new index to measure PSInn. The article analyses the evolution of PSInn across 324 elections held in 19 West European countries from 1945 to 2015 and its cumulative effects over time. Although in most countries the party landscape today is still very similar to the one appearing after World War II, data offer clear evidence of a sharp increase of innovation in the last few years.